2003
DOI: 10.1046/j.1365-2141.2003.04163.x
|View full text |Cite
|
Sign up to set email alerts
|

Two novel mutations, Q1053H and C1060R, located in the D3 domain of von Willebrand factor, are responsible for decreased FVIII‐binding capacity

Abstract: Summary. In type 2N von Willebrand disease (VWD), vonWillebrand factor (VWF) is characterized by a markedly decreased affinity for Factor VIII (FVIII), and the mutations responsible are essentially located in the D¢ domain of VWF. We report the identification, in seven unrelated French families, of two novel type 2N VWD mutations, Q1053H and C1060R (Gln290His and Cys297Arg in mature VWF sequence), in exon 24 of the VWF gene. These missense mutations have been identified in the heterozygous, homozygous or hemiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…15,23,32 Additionally, the R924Q change is controversial. Although this variation was originally reported as a polymorphism, 33 it is currently listed on the ISTH SSC VWF Database (http://www.vwf.group.shef.ac.uk/index.html) 24 as a type 2N VWD mutation and is scored as a benign variant by both of the in silico protein algorithms used in this study. Similarly, the R1315C missense mutation is listed in the VWF Mutation Database 24 as either a type 2M or unclassified mutation.…”
Section: Discussionmentioning
confidence: 99%
“…15,23,32 Additionally, the R924Q change is controversial. Although this variation was originally reported as a polymorphism, 33 it is currently listed on the ISTH SSC VWF Database (http://www.vwf.group.shef.ac.uk/index.html) 24 as a type 2N VWD mutation and is scored as a benign variant by both of the in silico protein algorithms used in this study. Similarly, the R1315C missense mutation is listed in the VWF Mutation Database 24 as either a type 2M or unclassified mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, it has been shown that rVWF-Cys1149Arg and rVWF-Cys1060Arg, which are involved in intrachain bonds, do not prevent formation of low and intermediate molecular weight VWF multimers. 17,32 To be able to fully assess the functioning of VWF, we believe that analysis of its ability to form WPBs, using expression of VWF in a heterologous system, should be part of a comprehensive study. The system should be such that expression of WT rVWF leads to formation of elongated organelles with internal striations that recruit appropriate membrane proteins and that respond to secretagogue.…”
Section: Discussionmentioning
confidence: 99%
“…Following electrophoresis, VWF was detected in the gel by means of rabbit antihuman VWF (Dako, Glostrup, Denmark) and visualized by means of alkaline phosphatase-conjugated swine antirabbit immunoglobulins (Dako, Denmark) and the AP Conjugate Substrate kit (Biorad, Hertfordshire, United Kingdom). 17 …”
Section: Vwf Multimer Analysismentioning
confidence: 99%
“…12 All the abovementioned mutations are located in the D' domain, but others have been reported in exon 17 13 or D3 domains. [14][15][16] Type 2N VWD patients are homozygotes or compound heterozygotes for different type 2N…”
mentioning
confidence: 99%